Helmintos e artrópodes de Vanellus chilensis (Molina, 1782), quero-quero, da região sul do Rio Grande do Sul - Avancini, Luciano Fagundes (2009)
Vanellus chilensis is a bird species of the family Charadriidae distributed across Central and South America. Despite its high abundance and broad distribution, there are few records of parasites on this species. Aiming to identify the helminths and arthropods that parasitize V. chilensis in southern Brazil, twenty eight birds were necropsied. For collection of ectoparasites, the birds were individually washed in water containing detergent. After that, they were necropsied and their organs were examined for helminths under a stereomicroscope. The helminths found and its respective prevalence, mean abundance and mean intensity were: Brevithominx asperodorsus (Enoplida, Capilariidae) 53.6%, 4.5 and 8.4; Heterakis psophiae (Oxyurida, Heterakidae) 39.3%, 1.0 and 2.55; Dispharynx nasuta (Spirurida, Acuariidae) 28.6%, 4.11 and 14.38; Echinostoma aphylactum (Echinostomida, Echinostomatidae) 17.9%, 0.64 and 3.6; Stomylotrema vicarium (Plagiorchiida, Stomylotrematidae) 10.7%, 0.25 and 2.33; Neivaia cymbium (Cyclocoeloidea, Cyclocoelidae) 7.1%, 0.14 and 2.0; Gyrocoelia perversa (Cyclophyllidea, Dioecocestidae) 60.7%. The Phthiraptera found were Actornithopilus sp. (Amblycera, Menoponidae) and Quadraceps guimaraesi (Ischnocera, Philopteridae). Another arthropod collected was the nasal mite Rhinonyssus sp. (Acarina, Rhinonyssidae). H. psophiae is cited for the first time parasitizing the order Charadriiformes in RS. B. asperodorsus, E. aphylactum, N. cymbium represent new records for Charadiidae in the State. This is the first report of natural infection in Charadriidae by the parasite S. vicarium in the region of study. The cestode G. perversa and the nematode D. nasuta are cited for the first time parasitizing V. chilensis in RS. The lice Actornithopilus sp. and Quadraceps guimaraesi are new records in RS as parasites of V. chilensis, which is also reported as a new host for the nasal mite Rhinonyssus sp